A proposed framework of sustainable manufacturing practice and sustainability performance among Malaysian SMEs in the manufacturing sector - Ahmad, Azliza; Hami, Norsiah; Mohd Shafie, Shafini; Mat Yamin, Fadhilah (2018)
There has been variation in the impact of sustainable manufacturing practice on sustainability performance.It also assumed that the sustainable manufacturing practice will enhance economic, environmental, and social sustainability of SMEs.Over the years, there seem to be widening limitation of sustainability in SMEs.There are hardly any studies that have formally documented the issue that have contributes to the widening gap between sustainable manufacturing practice and sustainability performance whether these will impact performance of SMEs.The objective of this paper is to propose a framework of improving sustainability performance through the implementation of sustainable manufacturing practices among SMEs in the manufacturing sector. The framework is developed based on the stakeholder theory and Triple Bottom Line (TBL) and supported by both conceptual and empirical past studies.Three propositions are developed in which relating to the relationships between five types of sustainable manufacturing practice and three dimensions of sustainability performance. This paper offers some contributions in both theoretical and managerial aspects.